Psoriasis, lymphoma and etanercept: is there a correlation? Psoríase, linfoma e etanercepte: existe correlação? - Ludmilla Queirós Miranda; Aline Lopes Bressan; Fernanda Valente da Silva Rehfeldt; Bárbara Nader Vasconcelos; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2012)
Psoriasis is a chronic inflammatory disease that can affect skin and joints. Their treatment varies depending on the severity and includes topical and systemic. Among the latter are the immunobiological that target the T cell We report a case that demonstrates the close relationship between psoriasis, lymphoma and biologic therapies. A psoríase é uma doença inflamatória crônica que pode afetar a pele e as articulações. Seu tratamento varia conforme a gravidade e inclui medicamentos tópicos e sistêmicos. Dentre os últimos estão os imunobiológicos, que têm como alvo a célula T. Relatamos um caso que demonstra a estreita relação entre a psoríase, o linfoma e os imunobiológicos.